The Moscow Karaite Community of the Twentieth Century (According to the Memoirs Recorded in the 1990S From the Old-Time Karaites of Moscow) - Sergei S. Mikhailov (Этническая культура, 2022)
The Karaites are one of the very small, but at the same time the most interesting ethno-confessional groups that appeared in the second half of the 19th – early 20th centuries. in a number of large cities of Central Russia, including Moscow. The purpose of the article is to acquaint readers and the scientific community with the results of a study of the Moscow diaspora of Karaites. When writing this article, the author primarily relied on field materials collected by him since 1993, by recording the memoirs of Moscow Karaites-old-timers. This ethnic group, whose representatives began to move from the middle of the XIX century. from the Crimea and, partly, Lithuania, professes a heretical stream of Judaism, founded in the 8th century. Babylonian Jew Anan ben David. Initially, the Russian (Crimean and Lithuanian) Karaites considered themselves part of the Jewish world, however, due to certain political reasons, they began to move away from Jewish identity, presenting themselves as a separate ethnic group professing an independent religion. The history of the Moscow Karaite diaspora is a very vivid example of such an evolution. Based on the method of field research, it was revealed that within the Karaite society, which numbered only a few hundred people, there were contradictions that did not contribute to unanimity in the diaspora and its religious parish. After 1989 there were no attempts to revive religious life. The activists of the community continued to develop new (in the author’s opinion – incorrect) assumptions regarding the origin of the Karaite people and their faith. At present, the Karaite diaspora, which never exceeded several hundred people in Moscow, is in the final stage of assimilation.